(untitled) (Research, Society and Development, 2023)
Dermal fillers with hyaluronic acid are a popular choice for improving aesthetic appearance with a low risk of late inflammatory reactions. However, reports of delayed hypersensitivity reactions following COVID-19 vaccination have raised concerns. While vaccination is critical to combating the pandemic, providers must obtain informed consent from patients about possible interactions with dermal fillers and risks of delayed hypersensitivity syndrome. Although rare, these reactions require professionals’ attention and preparation for proper management, ensuring patient safety. The study linking vaccination, orofacial harmonization, and dermal fillers with persistent intermittent delayed edema is clinically relevant, highlighting the need to understand interactions and prevent complications amidst the widespread adoption of vaccination against COVID-19. This narrative review of the literature aims to serve as a basis for a better understanding of the relationship between COVID-19, hyaluronic acid-based dermal fillers and persistent intermittent late edema.